The Tradition of Composing Travelogue in Okara - Sadiq, Shakeel Amjad (sourcecoder, 2024)
Travelogue pertains to and is included in such genre of Urdu literature which incorporates foreign literature, literature hunt, adventurous literature and travel diaries of other countries. These travelogues tend to highlight salient features of a particular country, it's literally environment, geography, socio-cultural values, economic and political situation alongside progress in respect of genres of literature. The purpose of writing a travelogue is to inform the readers about personal experiences and allied events. The actual purpose of a travelogue is to arouse longing to know more about alien land and narrate tales of a particular journey. Of allied types of such gener, the history of a Diary can be traced to 2nd century AD. A travelogue specifically comprises of events, expressions and particulars of a journey. Artistically, travelogue is a description which a traveller pens down either during the course of journey or at the end through his observations, feelings and at times at the instance of his heart. Therefore, the real motive of narrating a travelogue is not restricted to history, geography and living standards of a particular area. So with the passage of time, new innovations would be witnessed in connection with genre of travelogue.